Serum metabolomics profiling of commercially mixed functional foods—effects in Beta-amyloid induced rats measured using 1H NMR spectroscopy - Mohd Rosli, Nur Hasnieza; Yahya, Hanis Mastura; Ibrahim, Farah Wahida; Shahar, Suzana; Ismail, Intan Safinar; Ahmad Azam, Amalina; Rajab, Nor Fadilah (MDPI AG, 2020)
Functional foods such as pomegranate, dates and honey were shown by various previous studies to individually have a neuroprotective effect, especially in neurodegenerative disease such as Alzheimer's disease (AD). In this novel and original study, an 1H NMR spectroscopy tool was used to identify the metabolic neuroprotective mechanism of commercially mixed functional foods (MFF) consisting of pomegranate, dates and honey, in rats injected with amyloid-beta 1-42 (Aβ-42). Forty-five male albino Wistar rats were randomly divided into five groups: NC (0.9% normal saline treatment + phosphate buffer solution (PBS) solution injection), Abeta (0.9% normal saline treatment + 0.2 µg/µL Aβ-42 injection), MFF (4 mL/kg MFF treatment + PBS solution injection), Abeta-MFF (4 mL/kg MFF treatment + 0.2 µg/µL Aβ-42 injection) and Abeta-NAC (150 mg/kg N-acetylcysteine + 0.2 µg/µL Aβ-42 injection). Based on the results, the MFF and NAC treatment improved the spatial memory and learning using Y-maze. In the metabolic analysis, a total of 12 metabolites were identified, for which levels changed significantly among the treatment groups. Systematic metabolic pathway analysis found that the MFF and NAC treatments provided a neuroprotective effect in Aβ-42 injected rats by improving the acid amino and energy metabolisms. Overall, this finding showed that MFF might serve as a potential neuroprotective functional food for the prevention of AD.